Case study: meeting the demand for skilled precision engineers - Sansom, Christopher L.; Shore, Paul (Emerald Group Publishing Limited, 2008)
This paper aims to demonstrate how science and engineering graduates can be recruited and trained to Masters level in precision engineering as an aid to reducing the skills shortage of mechanical engineers in UK industry.
Keywords: Knowledge transfer; Postgraduates; Precision engineering; United Kingdom